2022
DOI: 10.1111/1744-9987.13805
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and severity of mental health problems and sexual dysfunction in hemodialysis patients before and during the COVID‐19 pandemic

Abstract: Introduction This study aimed to investigate the prevalence and severity of mental health problems and sexual dysfunction in hemodialysis patients before and during the COVID‐19 pandemic. Methods A total of 84 hemodialysis patients were evaluated in terms of Pittsburgh Sleep Quality Index, Beck Depression Inventory, International Index of Erectile Function (IIEF‐5), and Female Sexual Function Index (FSFI). Results Poor sleep quality (79.8%) and poor mental health status (62.7%) and higher likelihood of having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Similarly, Ghiasi et al (25) found that 60.4% of the patients had high levels of death anxiety in Iran and in Lebanon, Khoury et al (45) reported a high rate of depression in patients on hemodialysis (57.1%). In addition, Duru (46) revealed that rates of depression were significantly higher both war-zone conflicts or events have been suggested as possible explanations for the higher rates in these studies (45). Therefore, it is critical to assess depression and death anxiety in these patients because they have been linked to poor survival rates, a high risk of suicidal ideation, and non-adherence to therapy (47)(48)(49).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, Ghiasi et al (25) found that 60.4% of the patients had high levels of death anxiety in Iran and in Lebanon, Khoury et al (45) reported a high rate of depression in patients on hemodialysis (57.1%). In addition, Duru (46) revealed that rates of depression were significantly higher both war-zone conflicts or events have been suggested as possible explanations for the higher rates in these studies (45). Therefore, it is critical to assess depression and death anxiety in these patients because they have been linked to poor survival rates, a high risk of suicidal ideation, and non-adherence to therapy (47)(48)(49).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, Ghiasi et al ( 25 ) found that 60.4% of the patients had high levels of death anxiety in Iran and in Lebanon, Khoury et al ( 45 ) reported a high rate of depression in patients on hemodialysis (57.1%). In addition, Duru ( 46 ) revealed that rates of depression were significantly higher both before and after COVID-19 pandemic in Turkey (63.1% vs. 75.0% as overall, and 19.0% vs. 33.3% for moderate-to-severe depression). The Beck Depression Inventory scale and repeated exposure to traumatic war-zone conflicts or events have been suggested as possible explanations for the higher rates in these studies ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the COVID‐19 outbreak, haemodialysis patients travel between home and healthcare facilities (Yu et al, 2021 ), are at constant risk of contracting the virus, and are under tremendous pressure on their health and their families (Bulbul et al, 2022 ; Lv et al, 2022 ). In addition, loneliness, fear of death, and financial concerns are stressors that lead to anxiety and depression during the COVID‐19 pandemic, and the poor sleep quality caused by such stress is expected (Duru, 2022 ). As the results of this study show, every 7‐point increase in the PSS‐14 scale is associated with a 95% increased risk of poor sleep quality, which can be devastating for the prognosis of dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has seriously endangered the health of people around the world 7 . At the same time, serious effects emerged both physically and mentally in healthcare workers and patients working at an intense pace during the pandemic 8,9 . With the first cases to be seen in our country in March 2020, all health institutions were accepted as pandemic hospitals and it was recommended not to apply to health institutions when it is not necessary.…”
Section: Introductionmentioning
confidence: 99%